Children with mathematical difficulties cope with modelling tasks: what develops?. Issue 4 (19th May 2019) - Zubi, Ibtisam Abdelhalek; Peled, Irit; Yarden, Marva
ABSTRACT: This study investigates the participation and knowledge growth of children with mathematical difficulties as they work in groups with their classmates on a year-long sequence of modelling tasks. It involves observations of a class of 23 fifth graders, 9 of whom were identified as having difficulties in mathematics. All the students worked for 8 months on a sequence of 12 modelling task in heterogeneous groups. The findings show a gradual growth in modelling competencies and mathematical knowledge of the students with mathematical difficulties together with an increase in their contribution to the group. The growth in modelling competencies involved their ability to analyse situations and the growth of mathematical knowledge was evident in offering mathematical ideas during group work and in a better posttest performance. Student reflections indicated their awareness of these changes and of the appreciation of their ideas by their peers.